Human factors in cybersecurity: an in depth analysis of user centric studies - Hakimi, Musawer; Mohammad Mustafa Quchi; Abdul Wajid Fazil (Sean Institute, 2024)
This study delves into the intricate intersection of human behavior, cognition, and technology within the cybersecurity domain, aiming to enhance our understanding of the human-centric challenges influencing the effectiveness of cybersecurity measures. The primary objective is to unravel the nuanced landscape where human errors persist as a significant contributing factor to security breaches, emphasizing the need for a holistic comprehension of human factors. The study recognizes the evolving nature of work, with an increasing number of individuals operating from home, and the consequential challenges in managing human factors in the digital era. The blurring lines between private and public lives, coupled with the rise of social credit systems, necessitate a thorough examination of key elements intersecting with cybersecurity Employing a systematic literature review, this research methodically identifies, filters, and analyzes pertinent literature concerning human-centric factors in cybersecurity. The systematic approach involves the formulation of specific research questions guiding the study, strategic search plans targeting reputable databases, and meticulous study selection processes based on predefined criteria The study unfolds through a series of interconnected research questions, addressing the impact of human factors on operational efficiency, challenges in the adoption of human-centric approaches, and the ways in which human factors influence strategic decision-making in cybersecurity. The results shed light on the substantial contribution of understanding user behavior and cognitive processes to the development of tailored cybersecurity strategies. Challenges, such as security fatigue and the scarcity of psychology-based professionals, are addressed, advocating for human factors engineering and strategic initiatives to enhance education and training programs. In conclusion, embracing a human-centric paradigm emerges as imperative for organizations striving to fortify their defenses against dynamic and sophisticated cyber threats. Integrating technology with a profound understanding of human factors becomes the cornerstone for shaping a resilient and adaptive cybersecurity future.